Exegesis of Romans 13:1–7 and its appropriation to the new dispensation of the Second Republic of Zimbabwe - Gusha, Ishanesu S. (HTS teologiese studies, 2020)
The interpretation and appropriation of Romans 13:1–7 have been a challenge for generations because this text confuses Christians as to how they should relate and participate in the politics of the day. This article interprets the text in its historical and literary context before appropriating it to the Second Republic of Zimbabwe. The conclusion reached is that the text does not directly speak to church–state relations but rather should be understood in its context in Paul’s time. Appropriating the text to the Second Republic requires us to delineate whether the governing authorities of the Second Republic are doing the will of God or whether they are terrorising people into obedience. The article concludes that the text does not forbid people from resisting illegitimate and brutal governments and does not demand passive citizenship.Contribution: The article is an interpretation and appropriation of Romans 13:1–7 to the Second Republic of Zimbabwe. Appropriating the text to the Second Republic requires one to delineate whether the governing authorities are doing the will of God or not. It is within the scope of this theological journal that issues of church-state relationships and theological reflection should be addressed, hence this article fits well within this scope.